A coupled FE-FFT multiscale method for progressive damage analysis of 3D braided composite beam under bending load. (8th September 2019) - Fang, Guodong; Wang, Bing; Liang, Jun
Abstract: A more efficient multiscale coupling method is developed to study the progressive damage behavior of three dimensional (3D) braided composite beam. In the mesoscale, the fast Fourier transformation (FFT)-based method combining with variational principle is used to overcome the poor convergence for composites with large jumps of material properties. In the macro-scale, the mechanical response of the braided composites is analyzed by using finite element (FE) method, in which the stress and stiffness information of each material point can be transferred from the mesoscale results. It is verified that the predicted strength and dominated failure modes of the braided composites structure obtained by the proposed method combing with anisotropic stiffness degradation model are in good agreement with the experimental results. Meanwhile, the high computation efficiency is attractive for large complex structure taking into account the nonlinear mechanical behavior.